Mucosal Excision Instead of Fashioning Nasolacrimal Mucosae Flaps During External Dacryocystorhinostomy: A Pilot Study - Haefliger, I. O.; Tschopp, M.; Pimentel, A.-R. (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: To report results of a simplified external dacryocytorhinostomy procedure in which nasal and lacrimal sac mucosal flaps are simply removed instead of being sutured together.Patients and Methods:Design: Retrospective non-comparative case-series study. Participants: Fourteen consecutive outpatients patients undergoing external dacryocytorhinostomy. Intervention: Modified and simplified transcutaneous external dacryocytorhinostomy where basically the lacrimal sac and the nasal mucosae are widely excised in front of DCR’s osteotomy instead of being used to fashion nasolacrimal flaps. Outcome: Assessment of dacryocytorhinostomy anatomical patency by syringing and patient’s self-perception of epiphora symptoms improvement about twelve weeks and one year after surgery, as well as patient’s report of ocular air-reflux during Valsalva maneuver a year after surgery.Results: Syringing showed anatomic patency in 93 % and 92 % of patients twelve weeks (mean ± SD: 12 weeks ± 6 weeks) and one year (15 months ± 3 months) after surgery, respectively. One year after surgery, 62 % of patients reported ocular air-reflux. Twelve weeks and one year after surgery, mean symptom improvement was 82 % ± 17 % and 79 % ± 29 %, respectively. Furthermore, 79 % and 85 % of patients reported a postoperative improvement of their symptoms greater or equal to 80 % after twelve weeks and one year, respectively.Conclusions: Removing lacrimal sac and nasal mucosae in front of the osteotomy did not appear to have a major negative impact on the outcome of the external dacryocytorhinostomy. The findings of this pilot study need to be confirmed by a larger prospective trial.
Keywords: primary nasolacrimal duct obstruction (PNLDO); endonasal DCR; Toti; laser DCR; dacryocystectomy; epiphora; tearing eyes; watery eye